HAZARDOUS AND TOXIC WASTE MANAGEMENT IN THE COVID-19 REFERRAL HOSPITAL IN KENDARI CITY: HAZARDOUS AND TOXIC WASTE MANAGEMENT - Tahmar Tahmar; Erwin Azizi Jayadipraja; Ridwan Adi Surya (STIKes Mandala Waluya Kendari, 2022)
Background: Management of medical B3 waste during the COVID-19 pandemic is still very limited.At the Kendari City Regional General Hospital. B3 waste generation has increased from 24.324 kg in 2019 to 32.123 kg in 2020. In April 2021, the amount of B3 waste generation has reached 11,402 kg.There were several factors that affect the management of B3 waste. This study aims to determine the factors related to the management of hazardous and toxic waste (B3) at the Covid-19 Referral Hospital in Kendari City. Methods: This research used a cross sectional study design, conducted from August to September 2021. The samples in this study were 79 respondents taken by purposive sampling. Results: The statistical test suggests the value of X2count is 19,417 > X2 table is 3,841 and the value of the closeness relationship is Ф= 0,496. Conclusion: There is a moderate relationship between monitoring of management of hazardous and toxic waste (B3) at the Kendari City Covid-19 Referral Hospital.